UPAYA GURU DALAM MENINGKATKAN KREATIVITAS PESERTA DIDIK DI ERA GLOBALISASI - Ni Nengah Selasih (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Changes in time will bring changes in education which are dynamic and drastic so that the adaptation of educators with knowledge, skills, and values is highly needed to be invested to the students. Being a teacher is a challenging profession. A good teacher is a teacher who enjoys his work, believes in taught material, hard worker, spends a lot of time preparing lesson plans, uses parenting patterns, cares about his students' needs, and seeks to enable all students in learning. Being a creative and innovative teacher is not something that comes in just a second, it takes a long process. Therefore, to be an inspirational teacher, it can be done by keeping a commitment to keep giving creative, inspirational, and innovative spirit to the students. With the spirit given, teachers can create superior human creativity and competitive ability. Teachers are role models, role models for their students so that teachers should prioritize their desires to students, they must be creative, inspirational, innovative, and productive.